Analisis Manajemen Supervisi Kepala Sekolah pada SMA Negeri 1 Kepulauan Sula - Ajuan Umasugi; I. H Wenno; Vando. K. Makaruku; Sumarni Rumfot (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2024)
Supervision activities are intended to advance learning through professional improvement of teachers. Supervision encourages teachers to be more qualified and of course makes teaching and learning situations more effective, teachers become more flexible and ready to carry out their daily routine tasks. This research aims to find out how management supervises school principals. This study uses a qualitative method. The subjects in this research were 3 teachers and 1 principal at SMA Negeri 1 Sula Islands. Data collection was carried out through interviews, observation and documentation, to see how the principal supervised management was planned, implemented, evaluated, supported and inhibited.